Drug‐induced progressive multifocal leukoencephalopathy in multiple sclerosis: European regulators' perspective. Issue 2 (23rd January 2017) - Anton, R; Haas, M; Arlett, P; Weise, M; Balabanov, P; Mazzaglia, G; Prieto, L; Keller‐Stanislawski, B; Raine, J
Abstract : Progressive multifocal leukoencephalopathy (PML) has been associated with the use of a number of multiple sclerosis (MS) immunomodulatory therapies and has assumed a critical place in the evaluation of their benefit/risk. In this review, we discuss the European Union regulatory approach to drug‐induced PML in MS, highlight a number of key issues related to the current knowledge on PML, and outline possible paths to help progress the risk management of patients with MS at risk of PML.